DID 'UMAR IBN AL-KHATTAB ACT AGAINST ISLAM: BANI TAGHLIB TRIBE AS A CASE STUDY - Abu Munshar, Maher Y (Journal of Al-Tamaddun, 2010)
It was common practice for Muslim conquerors to negotiate pacts and treaties with conquered peoples. These treaties were quite similar in structure and content and reflected a spirit of tolerance towards non-Muslims. They consisted of three main elements: safety for their persons, property, and an assurance of freedom of religion. The simplicity of these agreements changed dramatically with the promulgation of a controversial agreement known as the Banū Taghlib peace treaty. This article is an attempt to present a critical analysis of the historical narratives of Muslim and non-Muslim scholars regarding Banū Taghlib treaty. It will also be an elaboration to the degree of tolerance attributed to Caliph 'Umar. Finally, this article will try to answer the following questions. Were the tribe of Banū Taghlib really exempted from paying the jizyah? Were they prohibited from baptising their children? Is it true that 'Umar instigated those conditions?